Morphological and molecular review of Jacob’s Mountain Stream Keelback Opisthotropis jacobi Angel & Bourret, 1933 (Squamata: Natricidae) with description of a sibling species from northern Vietnam - Ziegler, Thomas; David, Patrick; Ziegler, Tim N.; Pham, Cuong T.; Nguyen, Truong Q.; Le, Minh D. (Zootaxa, 2018)
New morphological data including hemipenis morphology is provided for Opisthotropis jacobi, a poorly known Mountain Stream Keelback from Vietnam and China, based on three newly collected individuals from Sa Pa (Lao Cai Province) and Tam Dao (Vinh Phuc Province) in northern Vietnam. In addition, morphological data from Vietnam is summarized based on the original description (Angel & Bourret 1933), on the overview book by Bourret (1936) and on a number of smaller, little-known contributions by the latter author along with re-examination of specimens deposited in the herpetological collection of the Muséum national d’Histoire naturelle, Paris. We also sequenced a fragment of the mitochondrial cytochrome b from the newly collected specimens of the Jacob’s Mountain Stream Keelback and performed molecular analyses of new and existing data of the genus. A recently discovered Opisthotropis population from Tay Yen Tu Nature Reserve in Bac Giang Province, northern Vietnam, which at the first glance resembled O. jacobi morphologically, is shown to diverge both genetically and morphologically from the existing species and is herein described as a new species. Opisthotropis voquyi sp. nov. is characterized by the combination of the following characters: internasal not in contact with loreal; one preocular; usually two postoculars; one anterior temporal; one posterior temporal; 7 or 8, rarely 9 supralabials; 25 maxillary teeth; subcaudals 74–86; 15 dorsal scale rows at neck, at midbody and before vent; body scales smooth or only with few faint keels; and dorsal scales being greyish, greyish-brown or brown in preservative, posteriorly more or less edged with pale greyish-brown. Phylogenetically, the new species is supported as a sister taxon to O. jacobi, but the two taxa are approximately 10% divergent based on cytochrome b data.